Analisis Perbedaan Karakteristik dan Perancangan Pekerjaan Manajer Sekolah Peternakan Rakyat (SPR) - Hafizah Khaerina; Anggraini Sukmawati; Muhammad Syamsun (Institut Pertanian Bogor, 2019)
The job design that is accommodative with the organization objective is vital to create efficiency in job performance, develop work satisfaction, and accelerate productivity. In SPR, a manager acts as a collective business coordinator. The objectives of this research were to analyze the difference of job characterization between SPR managers and Sentra PR managers and develop an appropriate job design. The necessary of identification of job characterization is to predict a successful job. The characterization was identified based on task, knowledge, social, and contextual characteristics. Samples were collected by interview and questionnaire. Sampling method used purposive sampling to 28 SPR managers in Indonesia, by then processed by t-test using SPSS versi 21.00. This research proved that SPR managers have a higher value in job characterization from several perspective, that is: task characteristic (task identity), knowledge characteristics (problem solving and skill variety) and social characteristic (feedback from others), however, there was no difference on contextual characteristic off those groups. The job design is created based on job characteristics such as task variety, problem solving, social support, and physical demands. The job design contains information about job description and qualification of SPR managers. Qualifications needed included education (bachelor degree from various majors), knowledge (about field conditions, local community, administration, reporting, and having knowledge of livestock will bean added value), skills and abilities (leadership and motivating farmers, initiatives and able to solve problems, entrepreneurial skills, good communication and negotiation skills, can operate computers and use the internet), and behavior (careful, disciplin, patient, innovative, creative, and hard-working).